Short-Term Effect of Conventional Versus Accelerated Corneal Cross-Linking Protocol on Corneal Geography and Stability - Sania Vidas Pauk; Sonja Jandroković; Dina Lešin Gaćina; Martina Tomić; Tomislav Bulum; Ana Pupić Bakrač; Tomislav Kuzman; Josip Knežević; Miro Kalauz (Medicina, 2023)
Purpose: To determine the 6-month effect of conventional (CXL30) and accelerated cross-linking with a UVA intensity of 9 mW/cm2 (CXL10) on corneal stability and to investigate whether there was a difference in ABCD grading system parameters regarding the two different procedures. Methods: Twenty-eight eyes of 28 patients with a documented keratoconus (KN) progression were included. Patients were selected to undergo either epi off CXL30 or CXL10. At the baseline and the follow-up visits after one (V1), three (V2), and six months (V3), the patients underwent complete ophthalmic examination and corneal tomography. Results: In the CXL30 group, all the parameters from the ABCD grading system significantly changed from baseline to V3; parameter A decreased (p = 0.048), B and C increased (p = 0.010, p < 0.001), and D decreased (p < 0.001). In the CXL10 group, there were no changes in parameters A (p = 0.247) and B (p = 0.933), though parameter C increased (p = 0.001) and D decreased (p < 0.001). After an initial decline after one month, visual acuity (VA) recovered on V2 and V3 (p < 0.001), and median maximal keratometry (Kmax) decreased in both groups (p = 0.001, p = 0.035). In the CXL30 group, there were significant changes in other parameters; average pachymetric progression index (p < 0.001), Ambrósio relational thickness maximum (ARTmax) (p = 0.008), front and back mean keratometry (p < 0.001), pachymetry apex (PA) (p < 0.001), and front elevation (p = 0.042). However, in the CXL10 group, there were significant changes only in ARTmax (p = 0.019) and PA (p < 0.001). Conclusion: Both epi-off CXL protocols showed similar short-term efficacy in improving VA and Kmax, halting the progression of KN, and both similarly changed tomographic parameters. However, the conventional protocol modified the cornea more significantly.